15-Deoxy-∆-12, 14-Prostaglandin J2 (15d-PGJ2), an Endogenous Ligand of PPAR-γ: Function and Mechanism. (1st August 2019) - Li, Jingjing; Guo, Chuanyong; Wu, Jianye
Abstract : 15-Deoxy-∆- 12, 14 -prostaglandin J2 (15d-PGJ2), a natural peroxisome proliferator-activated receptor- γ (PPAR- γ ) agonist, has been explored in some detail over the last 20 years. By triggering the PPAR- γ signalling pathway, it plays many roles and exerts antitumour, anti-inflammatory, antioxidation, antifibrosis, and antiangiogenesis effects. Although many synthetic PPAR- γ receptor agonists have been developed, as an endogenous product of PPAR- γ receptors, 15d-PGJ2 has beneficial characteristics including rapid expression and the ability to contribute to a natural defence mechanism. In this review, we discuss the latest advances in our knowledge of the biological role of 15d-PGJ2 mediated through PPAR- γ . It is important to understand its structure, synthesis, and functional mechanisms to develop preventive agents and limit the progression of associated diseases.